Fabrication and Thermoelectric Properties of Graphene/Bi2Te3 Composite Materials. (24th October 2013) - Liang, Beibei; Song, Zijun; Wang, Minghui; Wang, Lianjun; Jiang, Wan
Abstract : Graphene/Bi2 Te3 thermoelectric materials were prepared by spark plasma sintering (SPS) using hydrothermal synthesis of the powders as starting materials. The X-ray diffraction (XRD) and field emission scanning electron microscope (FE-SEM) were used to investigate the phase composition and microstructure of the as-prepared materials. Electrical resistivity, Seebeck coefficient, and thermal conductivity measurement were applied to analyze the thermoelectric properties. The effect of graphene on the performance of the thermoelectric materials was studied. The results showed that the maximum dimensionless figure of merit of the graphene/Bi2 Te3 composite with 0.2 vol.% graphene was obtained at testing temperature 475 K, 31% higher than the pure Bi2 Te3 .